Load‐based node ranked low‐energy adaptive clustering hierarchy: An enhanced energy‐efficient algorithm for cluster head selection in wireless sensor networks. (21st June 2021) - Mehta, Deepak; Saxena, Sharad
Abstract: A Wireless Sensor Network typically uses a large number of power‐constrained sensor nodes for sensing phenomenal data and for its processing. The lifetime of a sensor node is limited and this is a great challenge for researchers to sustain the network for a long time. Since, the data transmission from a sensor node to the base station is more power consuming, the hierarchical routing protocols play a major role in multihop communication and to prolong the network life time. It uses a clustering approach with an overhead of cluster head (CH) selection to attain this. This overhead needs proper addressing and to be reduced by some means. The work in this paper employs a new approach based on low‐energy adaptive clustering hierarchy (LEACH) and considers network load for electing CH in addition to number of links, residual sensor energy and distance. Here, energy and time are used for calculating load on a CH. The simulation results show that the proposed protocol performs better than LEACH, LEACH‐I, and NR‐LEACH algorithms on the parameters of average energy ratio throughput, end‐to‐end delay, packet delivery ratio, and a number of alive nodes.